The Effect Of Liquidity, Profitability, And Company Size On Audit Delay In Pharmaceutical Companies Listed On The Indonesia Stock Exchange - Malau, Sridevi Maharani; Fachrudin, Wan; Franita, Riska (Journal of Management, Economic, and Accounting, 2026)
The research analysis aims to examine the effect of financial performance on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. The research method used is quantitative by analyzing 11 companies in the pharmaceutical sub-sector. The data processing tool used is SPSS version 23. The results of the study indicate that liquidity has a positive and significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Profitability has a negative and significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Company size does not have a significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Liquidity, profitability, and company size have a significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange.